Climate Finance Research Trends: A Bibliometric Analysis of International Publications from 2010 to 2025 - Loso Judijanto (Westscience Press, 2026)
The main objective of this research is to identify the research space in the field of climate finance through bibliometric analysis of international literature on climate finance using scientific articles indexed in Scopus databases from 2010 to 2025. This paper uses the quantitative technique of scientific mapping along with the visualization techniques using VOSviewer to analyze the research production in the field of climate finance, collaboration trends, citation structure, and thematic evolution. This study shows an increased rate of research production in climate finance research after some key milestones reached in the global policies regarding climate change and sustainability. This study finds that co-authorship network analysis demonstrates the presence of high-quality collaboration among key countries and institutions in developed economies; however, developing nations are increasingly contributing in recent years. It shows the citation trend that identifies key citations forming the basis of research in the field of climate finance including aspects such as sustainable development, climate finance instruments, and policy. Finally, this research also shows the evolution of research keywords indicating transition from governance and mitigation-related issues to new themes in climate finance research such as adaptation, climate justice, and green financing innovations.